Long-Term Risk to Develop Hypertension in Women With Former Preeclampsia: A Longitudinal Pilot Study. (July 2014) - Ghossein-Doha, Chahinda; Spaanderman, Marc; van Kuijk, Sander M. J.; Kroon, Abraham A.; Delhaas, Tammo; Peeters, Louis
Introduction: Women with former preeclampsia (exPE) develop chronic hypertension 4 times more often than healthy parous controls. Women, destined to develop remote chronic hypertension, had increased left ventricular mass index (LVMI) and diastolic blood pressure (BP) prior to the onset of hypertension as compared to those remaining normotensive. However, longitudinal data on the progress of this increased LVMI in women destined to develop hypertension are lacking. Methods: We included 20 women with exPE and 8 parous controls. At both 1- and 14-year postpartum (pp), we performed cardiac ultrasound and determined circulating levels of the metabolic syndrome variables. Of 14-year pp, 7 (35%) former patients had developed chronic hypertension. We compared these 7 former patients with both the 13 former patients who remained normotensive and the 8 parous controls using the Mann-Whitney U test and Kruskal-Wallis analysis. Results: Women with hypertensive exPE differed from their normotensive counterparts by a higher incidence of early-onset preeclampsia (PE) in their index pregnancy and a higher rate of recurrence in next pregnancies. At 1-year pp, they also had high/normal BP and higher fasting insulin levels. At 14 years pp, the relative left ventricular wall thickness was higher, and the E/A ratio was lower, in the hypertensive group relative to those remaining normotensive. Conclusion: Women with exPE are at increased risk of developing chronic hypertension, when (1) the PE in the index pregnancy had an early-onset and/or recurred in next pregnancies and (2) the 1-year pp. Blood pressure was high normal. We also noticed that at 14 years pp, the hypertensive group showed signs of concentric left ventricular remodeling along with a decreased E/A ratio.